INTERPAKS-An Attempt to Aid Agricultural Communications Around the World - Jim Evans (Journal of Applied Communications, 1984)
Like many programs, the International Program for Agricultural Knowledge Systems (INTERPAKS) germinated in the high-acid soil of need and frustration.